A new species of the amphipod genus Quadrivisio (Senticaudata, Maeridae) from Chilika Lagoon, India - Bhoi, Gitanjali; Myers, Alan A.; Tarafdar, Lipika; Smita, Moili; Jena, Ajay Kumar; Patro, Shesdev (Zootaxa, 2023)
A new species of the amphipod genus Quadrivisio Stebbing, 1907, Quadrivisio chilikensis sp. nov. was collected from the Chilika Lagoon, east coast of India. The species was collected from seaweed Chaetomorpha sp.. The new species can be distinguished from other described species of the genus by the presence of a carina on pleonites and urosome, by the flagellum of antenna 2 being twice the length of peduncle article 5 and by pereopods 6 and 7 being equal in length.